Performance testing of active thermosiphon beams - Yeo, Adeline Xin Yi (2017)
With the recent energy shortage issues, there is greater commitment to protect the environment and reduce energy consumption. Conventional Heating, Ventilation and Air-Condition (HVAC) system uses Variable Air Volume (VAV) which requires a substantial amount of energy. Therefore, in recent years, there is more emphasis on Active and Passive Thermosiphon Beam (ATB/PTB) as these beams grant energy saving, cost reduction, indoor environment quality improvement, reduced space requirements etc. However, there are technical challenges for the application of ATB/PTB in tropical region in which the project team has developed a series of relevant solutions and methodologies. In this project, performance testing will be done on both PTB and ATB to compare the cooling capacity of the beam with relation to its average temperature difference. In addition, air straightener test will be carried out to compare the relationship between duct length of the beam and efficiency of displacement ventilation.